2019
DOI: 10.1016/j.clay.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A step ahead on efficient microwave heating for kaolinite

Abstract: The thermal evolution of kaolin clay under microwave radiation shows an unexpected large heating rate up to 500ºC/min for temperatures >650⁰C. Such heating rate is associated with a resistivity drop of >10 3 Ω.m observed after the dehydroxylation process. The high efficiency of the microwave heating effect is correlated with the presence of surface carriers that absorbs microwaves electromagnetic field and produces crystal heating by electron-phonon coupling or small polaron. The layered structure of the clay-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 32 publications
1
19
1
1
Order By: Relevance
“…Considering the high amount of greenhouse gases generated by this industry, 1 studies have investigated clean technologies for the production of red ceramics, looking for a sustainable material with better physical and mechanical properties and a more refined microstructure, 2 in addition to lower energy consumption 3 …”
Section: Introductionmentioning
confidence: 99%
“…Considering the high amount of greenhouse gases generated by this industry, 1 studies have investigated clean technologies for the production of red ceramics, looking for a sustainable material with better physical and mechanical properties and a more refined microstructure, 2 in addition to lower energy consumption 3 …”
Section: Introductionmentioning
confidence: 99%
“…Exploiting the many facets of microwave processing requires a thorough and comprehensive understanding of the underlying processes at atomic level for which new and complex instruments and measurement capabilities are needed. In this regard, several approaches have been developed for the in-situ monitoring of microwave reactions in combination with other characterization techniques for solid materials as X-Ray Diffraction, Neutron Scattering, FTIR or Raman Spectroscopy 1316 . Schmink and Leadbeater 15 and Vaucher et al .…”
Section: Introductionmentioning
confidence: 99%
“…Reinosa et al [31] reported that the thermal treatment of kaolinite below 200 °C resulted in dehydrated kaolinite, near 500–580 °C the dehydroxylation of kaolinite led to metakaolinite phases (mixture of SiO 2 , Al 2 O 3 and other oxides present as isomorphic substituents), while at temperatures higher than 980 °C mullite and amorphous silica were obtained (spinel phase).…”
Section: Resultsmentioning
confidence: 99%